Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To express the function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex] as a composition of two simpler functions, we need to find functions [tex]\( u \)[/tex] and [tex]\( y \)[/tex] such that [tex]\( y \)[/tex] is expressed in terms of [tex]\( u \)[/tex]. Essentially, we want to split the original function into two functions where one depends on [tex]\( x \)[/tex] and the second depends on the first function.
Given the original function:
[tex]\[ y = \sqrt{x^{19} + 9} \][/tex]
We will check each pair of simpler functions to see if they correctly decompose this function.
1. [tex]\( u = x^{19} + 9 \)[/tex] and [tex]\( y = \sqrt{u} \)[/tex]
[tex]\[ u = x^{19} + 9 \quad \Rightarrow \quad y = \sqrt{u} = \sqrt{x^{19} + 9} \][/tex]
This pair is valid because substituting [tex]\( u \)[/tex] into [tex]\( y \)[/tex] results in the original function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex].
2. [tex]\( u = x + 9 \)[/tex] and [tex]\( y = \sqrt{u^{19}} \)[/tex]
[tex]\[ u = x + 9 \quad \Rightarrow \quad y = \sqrt{u^{19}} = \sqrt{(x+9)^{19}} \][/tex]
This pair does not match the original function because [tex]\( \sqrt{(x+9)^{19}} \neq \sqrt{x^{19} + 9} \)[/tex].
3. [tex]\( u = \sqrt{x} \)[/tex] and [tex]\( y = u^{19} + 9 \)[/tex]
[tex]\[ u = \sqrt{x} \quad \Rightarrow \quad y = u^{19} + 9 = (\sqrt{x})^{19} + 9 = x^{9.5} + 9 \][/tex]
This pair does not match the original function because [tex]\( x^{9.5} + 9 \neq \sqrt{x^{19} + 9} \)[/tex].
4. [tex]\( u = x^{19} \)[/tex] and [tex]\( y = \sqrt{u + 9} \)[/tex]
[tex]\[ u = x^{19} \quad \Rightarrow \quad y = \sqrt{u + 9} = \sqrt{x^{19} + 9} \][/tex]
This pair is also valid because substituting [tex]\( u \)[/tex] into [tex]\( y \)[/tex] results in the original function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex].
5. [tex]\( u = \sqrt{x + 9} \)[/tex] and [tex]\( y = u^{19} \)[/tex]
[tex]\[ u = \sqrt{x + 9} \quad \Rightarrow \quad y = u^{19} = (\sqrt{x + 9})^{19} = (x + 9)^{9.5} \][/tex]
This pair does not match the original function because [tex]\( (x + 9)^{9.5} \neq \sqrt{x^{19} + 9} \)[/tex].
Thus, the pairs of functions that correctly express [tex]\( y = \sqrt{x^{19} + 9} \)[/tex] are:
[tex]\[ u = x^{19} + 9 \quad \text{and} \quad y = \sqrt{u} \][/tex]
[tex]\[ u = x^{19} \quad \text{and} \quad y = \sqrt{u + 9} \][/tex]
These pairs decompose the original function as desired.
Given the original function:
[tex]\[ y = \sqrt{x^{19} + 9} \][/tex]
We will check each pair of simpler functions to see if they correctly decompose this function.
1. [tex]\( u = x^{19} + 9 \)[/tex] and [tex]\( y = \sqrt{u} \)[/tex]
[tex]\[ u = x^{19} + 9 \quad \Rightarrow \quad y = \sqrt{u} = \sqrt{x^{19} + 9} \][/tex]
This pair is valid because substituting [tex]\( u \)[/tex] into [tex]\( y \)[/tex] results in the original function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex].
2. [tex]\( u = x + 9 \)[/tex] and [tex]\( y = \sqrt{u^{19}} \)[/tex]
[tex]\[ u = x + 9 \quad \Rightarrow \quad y = \sqrt{u^{19}} = \sqrt{(x+9)^{19}} \][/tex]
This pair does not match the original function because [tex]\( \sqrt{(x+9)^{19}} \neq \sqrt{x^{19} + 9} \)[/tex].
3. [tex]\( u = \sqrt{x} \)[/tex] and [tex]\( y = u^{19} + 9 \)[/tex]
[tex]\[ u = \sqrt{x} \quad \Rightarrow \quad y = u^{19} + 9 = (\sqrt{x})^{19} + 9 = x^{9.5} + 9 \][/tex]
This pair does not match the original function because [tex]\( x^{9.5} + 9 \neq \sqrt{x^{19} + 9} \)[/tex].
4. [tex]\( u = x^{19} \)[/tex] and [tex]\( y = \sqrt{u + 9} \)[/tex]
[tex]\[ u = x^{19} \quad \Rightarrow \quad y = \sqrt{u + 9} = \sqrt{x^{19} + 9} \][/tex]
This pair is also valid because substituting [tex]\( u \)[/tex] into [tex]\( y \)[/tex] results in the original function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex].
5. [tex]\( u = \sqrt{x + 9} \)[/tex] and [tex]\( y = u^{19} \)[/tex]
[tex]\[ u = \sqrt{x + 9} \quad \Rightarrow \quad y = u^{19} = (\sqrt{x + 9})^{19} = (x + 9)^{9.5} \][/tex]
This pair does not match the original function because [tex]\( (x + 9)^{9.5} \neq \sqrt{x^{19} + 9} \)[/tex].
Thus, the pairs of functions that correctly express [tex]\( y = \sqrt{x^{19} + 9} \)[/tex] are:
[tex]\[ u = x^{19} + 9 \quad \text{and} \quad y = \sqrt{u} \][/tex]
[tex]\[ u = x^{19} \quad \text{and} \quad y = \sqrt{u + 9} \][/tex]
These pairs decompose the original function as desired.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.